2023
DOI: 10.1111/jdv.19238
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to biologic therapy before and during pregnancy in patients with psoriasis: Systematic review and meta‐analysis

V. Sánchez‐García,
R. Hernández‐Quiles,
E. de‐Miguel‐Balsa
et al.

Abstract: Biologicals have transformed the management of severe disease phenotypes in psoriasis and are often prescribed in women of childbearing age. However, information on safety of biologicals in pregnancy are lacking. We conducted a systematic review and meta‐analysis aimed to describe the characteristics and pregnancy outcomes in women with psoriasis exposed to biologics within 3 months before or during pregnancy, and to estimate the pooled prevalence of spontaneous, elective and total abortions, and congenital ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…O’Byrne et al found that for TNF-α inhibitors, there was still no definitive statistical link between exposure to biologics and the development of a congenital abnormality and that its incidence was 4% overall [ 32 ]. Similarly, a meta-analysis of pregnancies exposed to biologics used in psoriasis indicated that 3% reported congenital abnormalities [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…O’Byrne et al found that for TNF-α inhibitors, there was still no definitive statistical link between exposure to biologics and the development of a congenital abnormality and that its incidence was 4% overall [ 32 ]. Similarly, a meta-analysis of pregnancies exposed to biologics used in psoriasis indicated that 3% reported congenital abnormalities [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 However, currently reported safety information on the use of biologics in patients with generalized pustular psoriasis and who are pregnant, planning to become pregnant, or who are breastfeeding, remains limited. 4 We herein report successful treatment with ustekinumab (STELARA ® ) in a pregnant patient with generalized pustular psoriasis.…”
Section: Introductionmentioning
confidence: 92%
“…There is mixed evidence for the use of biologics prior to pregnancy in terms of conception rates. In the psoriasis population, exposure to biologics during conception does not appear to have any adverse reactions, but more research in the field and in HS populations is warranted ( 69 ).…”
Section: What Concerns Should Gps Have During Biologic Usage?mentioning
confidence: 99%